Status Kewarisan Kafir Khafy Perspektif Hukum Islam: The Inheritance Status of Khafy disbelief from Islamic Legal Perspective - Muttazimah, Muttazimah; Munira, Munira; Annisa Miftahussaadah; Muhamad Saddam Nurdin (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to find out how the inheritance of someone whose unknown disbelief or deliberate is concealed. This research uses a type of qualitative (non-statistical) descriptive research, which focuses on the study of manuscripts and texts, using normative approach methods. The findings of the research are as follows: The term unbeliever khafy is not a term in the law of inheritance, but it is a phenomenon that often occurs when there are members of families of different religions. A murderer who hides his iniquity will be condemned to disbelief. When the unbeliever is an heir, he is punished as his family is known. When the news of disbelief comes to them and it is revealed that the heir had changed faith or disbelieved, the scholars differ in the matter. But what is agreed by the majority of scholars (Imam Mālik, Imam Syāfi’i, and Imam Aḥmad) is the view that the murderer cannot inherit his property to the heir and does not have the right to receive the inheritance as the original disbeliever. The riches of the unbelievers shall be the property of the faithful, whether it be in Islam or when it is in disobedience. When the unbeliever is an inheritor, it is necessary to see when he fails. If he dies before or after the heir, he shall be condemned to disbelief, and his inheritance shall be returned to the rightful heir. Those who disbelieve will be punished by their wages and will be given an inheritance.